A Novel Variant of DeSanto-Shinawi Syndrome with Joint Manifestations - Branco, J (2022)
variable degrees of developmental delay and intellectual disability that were recently delineated as DeSanto- Shinawi syndrome (OMIM 616708). We describe a patient with DeSanto-Shinawi syndrome caused by a novel frameshift variant in WAC gene (NM_016628.4(WAC):c.1689del (p.Phe563Leufs*6)). As noted in cases previously reported, our patient phenotype included facial dysmorphism, intellectual disability, behavioral problems, feeding difficulties, hirsutism, constipation and astigmatism. She also had limited range of motion of joints since birth and Juvenile Idiopathic Arthritis diagnosed at eleven years old. Although in the last years some additional features were reported in DeSanto-Shinawi syndrome, joint manifestations have not been previously described. As limited range of motion of joints was reported since birth with no correlation with arthritis onset, it could be a new clinical feature. Polyarthritis in this patient can be only a coincidence, since there is a first degree relative with psoriasis, or might be related to WAC mutation. Indeed, WAC encodes a protein that plays a vital role in autophagy. It has already been demonstrated that WAC haploinsufficiency leads to increased autophagy and, according to different authors, increased autophagy may display a pathogenic role in several autoimmune disorders such as Rheumatoid Arthritis and Juvenile Idiopathic Arthritis. Thus, WAC haploinsufficiency may have contributed to autoimmune disorder in this patient.